Hubungan Faktor Sosiodemografi dengan Kejadian Anemia Mikrositik Hipokromik pada Ibu Hamil di RSIA Permata Bunda Kabupaten Pandegelang - Muhammad Fauzan Iqbal; Sutarto Sutarto; Anisa Nuraisa Jausal; Rodiani Rodiani; Reni Indriyani (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2026)
Anemia in pregnant women remains a significant public health problem and contributes to increased maternal and fetal morbidity and mortality. Microcytic hypochromic anemia is the most common type of anemia during pregnancy and is associated with various factors, including sociodemographic characteristics. This study aimed to analyze the association between sociodemographic factors and microcytic hypochromic anemia status among pregnant women at Permata Ibunda Mother and Child Hospital, Pandeglang Regency, in 2024. This study used an analytical observational design with a case-control approach. A total of 74 pregnant women were included and divided into case and control groups based on anemia status. Data were obtained from medical records and analyzed using the Chi-Square test with a significance level of 0.05. The results showed that age (p=0.027), education (p=0.032), healthcare class (p=0.035), and residential area (p=0.030) were significantly associated with microcytic hypochromic anemia, while occupation (p=0.127) was not significantly associated. Pregnant women with non-ideal age, lower educational level, lower healthcare class, and those living in rural areas had a higher risk of developing anemia. In conclusion, certain sociodemographic factors are associated with the occurrence of microcytic hypochromic anemia among pregnant women. Therefore, comprehensive interventions through health education, improved access to healthcare services, and enhancement of socioeconomic conditions are needed to reduce the prevalence of anemia in pregnant women.